Performance improvement in a tubular heat exchanger by punched delta-winglet vortex generators - Khanoknaiyakarn, C.; Promvonge, P.; Thianpong, C.; Skullong, S. (My University, 2018)
A novel tubular heat exchanger incorporated with punched delta-winglet vortex generators (called perforated delta-winglet vortex generator, P-DWVG) is proposed for improving its thermal performance and energy saving. The P-DWVG elements are punched out from a straight tape having its width nearly equal to the tube diameter before insertion. The main aim at employing the P-DWVG insert is to produce counter-rotating vortices along the tube to promote turbulence intensity inside as well as to transport the cold fluid at the central core to the near-wall regions. The experiment was performed to study thermal behaviors in a uniform heat-fluxed tube inserted with P-DWVGs. The P-DWVGs with the attack angle of 45° were mounted periodically with three different blockage ratios (BR = 0.1, 0.2 and 0.3) and two pitch ratios (PR = 2 and 3). Air as the test fluid was varied to obtain turbulent airflow for Reynolds number (Re) in a range of 4,150-25,500. The experimental results show that the P-DWVG provides a considerable increase in the rate of heat transfer around 3.1-4.01 times whereas friction factor increases around 11.44- 34.23 times higher than the plain tube. To assess the real benefits of P-DWVGs, thermal performance factor (TEF) is examined and in the range of 1.39-1.48 where its maximum is at BR = 0.1 and PR = 2.